Pretty woman [videorecording (DVD)] - Marshall, Garry; Gere, Richard, 1949-; Roberts, Julia, 1967-; Bellamy, Ralph, 1904-1991 (Touchstone Home Video ; Distributed by Buena Vista Home Entertainment, 2005)
A corporate raider pays a gorgeous hooker to be his escort for a business week in Beverly Hills...and then falls for her. Fifteenth anniversary special edition packed with all-new, never-before-seen bonus features.